2001
DOI: 10.1093/jnci/93.5.347
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ceramide Metabolism--a Strategy for Overcoming Drug Resistance

Abstract: Inherent or acquired drug resistance, which frequently characterizes cancer cells, is caused by multiple mechanisms, including dysfunctional metabolism of the lipid second messenger ceramide. Ceramide, the basic structural unit of the sphingolipids, plays a role in activating cell death signals initiated by cytokines, chemotherapeutic agents, and ionizing radiation. Recent discoveries about the metabolism of ceramide suggest that this agent may have an important influence on the effectiveness of various cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
256
0
12

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(277 citation statements)
references
References 110 publications
7
256
0
12
Order By: Relevance
“…Treatment of cancer cells with radiation and chemotherapeutics such as vincristine, daunorubicin, gemcitabine, and etoposide result in ceramide accumulation in the cells as a secondary effect of these therapeutics [187]. Decreased ceramide levels result in the development of drug resistance in cancer cells [188]. In vitro studies indicated that treatment of cancer cells with ceramide triggers the release of cytochrome-c from the mitochondria [189].…”
Section: Bioactive Sphingolipids In Apoptotic Pathwaysmentioning
confidence: 99%
“…Treatment of cancer cells with radiation and chemotherapeutics such as vincristine, daunorubicin, gemcitabine, and etoposide result in ceramide accumulation in the cells as a secondary effect of these therapeutics [187]. Decreased ceramide levels result in the development of drug resistance in cancer cells [188]. In vitro studies indicated that treatment of cancer cells with ceramide triggers the release of cytochrome-c from the mitochondria [189].…”
Section: Bioactive Sphingolipids In Apoptotic Pathwaysmentioning
confidence: 99%
“…25,26 The mechanism behind this interaction is not completely understood, but it is likely that mitochondrial cytochrome c release is important to the induction of apoptosis by 4HPR and chemotherapy. 21,27,28 Previous work has shown that TRAIL induces direct caspase activation and that, in some cells, TRAIL also induces mitochondrial cytochrome c release and caspase activation. 29 Thus, we investigated if 4HPR could enhance TRAIL-mediated apoptosis in ovarian cancer cells, which are resistant to TRAIL-mediated apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…One strategy to treat MRD is to restore sensitivity to chemotherapeutic drugs. It has been recently reported, that a MDR phenotype is often associated with aberrant ceramide metabolism [77]. In this context, TNF-α-resistant MCF7 breast cancer cells have been characterized by the inability of their neutral or acidic sphingomyelinases to generate ceramide [78].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in breast and in prostate cancer, that treatment of MDR cancer cells with either inhibitors of GCS or inhibitors of S1P restored sensitivity to chemotherapeutic agents [71,77,79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation